Pemberdayaan Masyarakat Melalui Peningkatan Budidaya Kacang Tanah di Kampung Jagebob Raya - Adrianus Adrianus; Abdul Rizal; Anwar Anwar; Mani Yusuf; Suwarjono Suwarjono (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Kampung Jagebob Raya is one of the villages that has Natural Resources (SDA) and Human Resources (HR) which have the potential to be developed. This can be seen from the carrying capacity and availability of land for peanut cultivation. In addition, the majority of people have livelihoods as farmers. Commodities cultivated by the people in this village include corn, chili, long beans and peanuts. Peanut is a palawija crop that has a fairly high selling value. Apart from being a source of protein, carbohydrates, vitamins, it is also used as a cooking spice, boiled peanuts, fried peanuts, crunchy peanuts, and other snacks. This potential can encourage people to be more active in increasing the production and productivity of peanuts. Empowering the community through cultivating peanuts is one of the efforts to improve business skills in terms of innovation, promotion, processing and marketing. The method of implementing peanut cultivation activities in Kampung Jagebob Raya was carried out in two stages, namely socialization and demonstration plots. Socialization with the local government is to agree on the implementation of community service activities while the demonstration plot is to assist farmers in cultivating land, planting, pest control to post-harvest. Community empowerment activities have a positive value for farmers in Kampung Jagebon Raya. In addition to increasing knowledge, farmers can be empowered and help improve the community's economy.